Functional remodelling of perinuclear mitochondria alters nucleoplasmic Ca2+ signalling in heart failure. (21st November 2022) - Voglhuber, Julia; Holzer, Michael; Radulović, Snježana; Thai, Phung N.; Djalinac, Natasa; Matzer, Ingrid; Wallner, Markus; Bugger, Heiko; Zirlik, Andreas; Leitinger, Gerd; Dedkova, Elena N.; Bers, Donald M.; et al.
Abstract : Mitochondrial dysfunction in cardiomyocytes is a hallmark of heart failure development. Although initial studies recognized the importance of different mitochondrial subpopulations, there is a striking lack of direct comparison of intrafibrillar (IF) versus perinuclear (PN) mitochondria during the development of HF. Here, we use multiple approaches to examine the morphology and functional properties of IF versus PN mitochondria in pressure overload-induced cardiac remodelling in mice, and in non-failing and failing human cardiomyocytes. We demonstrate that PN mitochondria from failing cardiomyocytes are more susceptible to depolarization of mitochondrial membrane potential, reactive oxygen species generation and impairment in Ca 2+ uptake compared with IF mitochondria at baseline and under physiological stress protocol. We also demonstrate, for the first time to our knowledge, that under normal conditions PN mitochondrial Ca 2+ uptake shapes nucleoplasmic Ca 2+ transients (CaTs) and limits nucleoplasmic Ca 2+ loading. The loss of PN mitochondrial Ca 2+ buffering capacity translates into increased nucleoplasmic CaTs and may explain disproportionate rise in nucleoplasmic [Ca 2+ ] in failing cardiomyocytes at increased stimulation frequencies. Therefore, a previously unidentified benefit of restoring the mitochondrial Ca 2+ uptake may be normalization of nuclear Ca 2+ signalling and alleviation of altered excitation–transcription, which could be an important therapeutic approach to prevent adverse cardiac remodelling. This article is part of the theme issue 'The cardiomyocyte: new revelations on the interplay between architecture and function in growth, health, and disease'.